'The Destroying Angel of Tempest': the Sea in Villette. (April 2013) - Swann, Mandy
Abstract : In Charlotte Brontë's Villette, the sea represents the repressed intellectual power, romantic fantasies, resentment and fury of Lucy Snowe. Ocean images in Villette are entrenched within the ideological and iconographical heritage of Homer and the Bible. In the Odyssey and the Bible the sea is associated with dichotomous extremes of beauty and hideousness, gentleness and violence, and salvation and punishment. Charlotte's seas of feminine desire and intellect reflect these dichotomous extremes. With Homeric echoes, Charlotte uses ocean imagery to depict the excesses of passion, insanity and hopelessness that result from the complete liberty of female emotion and intellect. Yet, with biblical echoes, she also uses ocean imagery to create the Christian framework she establishes in order to control these excesses. Ultimately, Charlotte makes the sea in this novel the cognate for human suffering, which she presents as simultaneously ugly, intolerable and exquisite.